Kemitraan dalam Pengelolaan Geowisata Goa Pindul di Kabupaten Gunungkidul - Oqi Dewi; Eny Boedi Orbawati; Fadlurrahman Fadlurrahman; Seiren Ikhtiara; Joko Tri Nugraha; Ari Mukti (Universitas Sultan Ageng Tirtayasa, 2023)
Partnership is a concept of cooperation used by the Gunungkidul Regency Tourism Office, BUMDes Maju Mandiri, and tour guide business (pokdarwis) in managing the Pindul cave. Through this partnership, the management of Pindul cave is expected to be better, but in reality there are still disobedience and lack of openness in partnership. This study aims to provide an overview of partnership between actors in the management of Pindul cave in Gunungkidul Regency. The research method used in this study is qualitative using a descriptive approach. The results showed that the optimization of partnership between actors in the management of Pindul cave runs only on the principle of mutual benefits, namely absorption of labor, reducing unemployment, and increasing the income of each actors. Meanwhile, the principle of equality and opennes of partnership has not run optimally as indicated by coordination noncompliance, and lack of openness in partnership.